Manajemen Ekstrakurikuler Pendidikan Lingkungan Hidup Generasi Sadar Iklim di Sekolah Menengah Pertama Negeri 1 Panti - Nafirotul Hasanah; Nur Ittihadatul Ummah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The climate crisis and rapid social changes demand the education sector to produce a generation that is environmentally conscious and responsible. The Environmental Education Extracurricular Program "Generasi Sadar Iklim" (Gensalim) at SMP Negeri 1 Panti was established as an effort to instill ecological awareness from an early age. Effective management plays a key role in ensuring the sustainability and achievement of environmental education goals. This research employed a qualitative method with a descriptive approach through interviews, observations, and documentation. The findings indicate that planning was carried out by involving the principal, supervising teachers, and students through needs analysis, goal setting, work program development, activity scheduling, attendance listing, and the provision of facilities and infrastructure. Furthermore, the organizing process was conducted through coordination between the principal, the student affairs vice principal, and the supervisors, marked by the appointment of supervisors, the formation of organizational structure, and the distribution of tasks. The implementation involved all Grade VII and VIII students through class representatives using various learning approaches such as lectures, video screenings, and field practices. Finally, the evaluation was conducted both internally by the school and externally by related institutions.